Association between the negative hyoid triangle and oral breathing - Flores Toro, Daniela (2020)
Objective. The objective of this study was to evaluate the association between the presence of the hyoid triangle negative and oral breathing. Methods. We analyzed a total of 100 lateral teleradiographs, 50 belonging to patients with oral breathing and 50 with nasal breathing. Of these, 70% corresponded to female patients (n=70) and 30% to male patients (30). 59% corresponded to patients between 20 and 30 years, 21% between 10-20 years, 15% between 30-40 years and 5% between 40-50 years old. The inclusion criteria were clinical records of patients of both sexes between 15 and 50 years of age, who have profile teleradiographs and in which their type of breathing (oral or nasal) has been recorded. The exclusion criteria were clinical records of patients in whom the teleradiography is in digital format, with positioning or damaged errors or belonging to subjects who have diagnosed genetic syndromes and who have not received previous orthodontic/ orthopedic treatment. The x-rays were analyzed by cephalometric technique of Rocabado. Descriptive statistical analysis was performed and Chi2 statistical test through contingency tables. Results. It was found that there is a statistically significant association (p < 0.001) between the presence of a triangle hyoid negative and oral breathing, being the female patients (p < 0.001) of 10 to 20 years which were more frequent (81%). Conclusions. It was possible to conclude that there is a statistically significant association between the presence of negative hyoid triangle and oral breathing, which seems to be related to sex and age.